Soviet Monuments in Urban Space: Reformatting the Past - Denis S. Artamonov (Corpus Mundi)
The article is devoted to the problem of transformation of the role of Soviet monuments in modern urban space. The author examines the changes in their perception in the context of cultural, social and political processes, and also shows how monuments are used as an arena for memorial conflicts. Special attention is paid to the loss of their memorial significance and their inclusion in individual and folklore practices reflecting changes in the identity of society. The purpose of the study is to analyze the mechanisms of reformatting Soviet monuments, their symbolic significance and influence on collective memory. As a result, the author proves that monuments originally created to promote ideological values acquire new symbolic functions over time. In modern conditions, they often lose their original commemorative role, becoming elements of urban folklore, tourist sites or even the basis for Internet content. In addition, their transformation, associated with physical changes or recoding of meanings, turns monuments into a tool for rethinking the past and expressing modern identity. It is noted that Soviet monuments are becoming objects of memorial conflicts, especially in post-Soviet countries, where changes in memory policy cause discussions in society. The conclusions of the article will be useful to researchers engaged in the study of memory, cultural policy and urbanism, as well as to anyone interested in the history of the Soviet heritage. The article emphasizes the importance of rethinking the past in shaping the modern urban environment and identity.